Agility: Organisational Learning & Change - Cockburn, Darren Brian (2006)
The concept of agility has recently emerged as an important way of framing the strategic challenges facing organisations in the twenty-first century. Continuous change is the only guaranteed constant and we must embrace it to remain competitive. Being agile is about being well positioned to respond to opportunities and issues quickly. Many customers are demanding bespoke solutions (mass customisation) rather than static products at low prices (mass production). Fixed product structures perish within our uncertain environment and organisations need to leverage a flexible product portfolio, which can be configured to deliver bespoke solutions to customers at high speed and low cost. This approach to delivering solutions can also be used to exploit new opportunities in the market and obtain a first mover advantage. It requires considerable effort and change to make an organisation more agile. Not all organisations and academics share a common definition of agility. The definition provided from Goldman et al (1995) will serve as a baseline for the research: For a company, to be agile is to be capable of operating profitably in a competitive environment of continually, and unpredictably, changing customer opportunities. This report presents two original frameworks covering organisational agility, which are the result of an extensive review of related literature. These are then refined through empirical research within Experian, which is a global information solutions organisation. The frameworks are combined to form a single framework that represents the best of literature and practice. The current state and recommended future state within Experian are defined from an agility standpoint. Finally, conclusions are drawn that examine the extent to which agility is a new and useful concept and an alternative definition is proposed.